Analisis Faktor-Faktor yang Mempengaruhi Tingkat Pengangguran Terbuka di Sumatera Menggunakan Metode Multivariate Adaptive Regression Spline (MARS) - Liska Andani; Dewi Murni (UNIVERSITAS NEGERI PADANG, 2020)
bstract— Open Unemployment Rate (OUR) is defined as the percentage ratio of the number of open unemployment to the total labor force. In 2018, for 5 provinces in Sumatra, those are the provinces of Riau Islands, Aceh, Riau, North Sumatra and West Sumatra, the OUR value was relatively high and exceeded the OUR value in Indonesia, which was 5.34 percent. This study aims to look at the significant factors that influence OUR in Sumatra in 2018 at the best model obtained with research data in the form of secondary data obtained from the BPS-Statistics and analyzed using the Multivariate Adaptive Regression Spline (MARS) method. The best model obtained is the result of a combination of BF= 28, MI= 2, MO= 4 with the Generalized Cross Validation (GCV) value of 0,09413 as the minimum GCV value and the factors that influence the OUR, those are the independent variables X1, X2, X4, X6, and X7 with R 2 adj of 81.4 percent and factors that did not affect the independent variable were the number of households (X3) and the average expenditure per capita a month for food (X5).Keywords— open unemployment rate, MARS, GCV.